SPECIALIZED MEDICAL FORCE - FEM / SPECIALIZED MEDICAL CARE SERVICE – SAME: A PROPOSAL FOR CREATION AND INSTITUTIONALIZATION BY THE BRAZILIAN MINISTRY OF HEALTH - de Sousa Santos, Eriegly; Sereide Ferreira da Silva , Sandra (Health and Society, 2023)
In light of the growing concerns related to public health in Brazil, from any perspective, in any scenario that can be projected for the future, there is a substantial increase in demands and, with this, the need for a larger, better workforce. qualified and with expanded skills. In that regard. Strategic prospecting studies are fundamental for planning public policies, especially with regard to the workforce for the Unified Health System. Therefore, this study aims to set up a Specialized FEM Medical Force, with a Specialized Medical Care Service - Nationwide SAME linked to the Brazilian Ministry of Health. This study will be carried out through the analysis of the legislation concerning the Federal Public Health Legislation in Brazil, in the analysis of the National Emergency Care Policy of the Unified Health System – SUS, as well as other national, state and municipal documents, as well as consultations on the official websites of these federative entities. The expected results, among other results, are: meeting the needs of the population with specialized care in all areas of medicine; compose a specialized assistance framework for the less favored population and considered vulnerable from a financial point of view and be a public utility service available to the population, with regard to national emergency care in situations of disasters and public calamities.